Bilateral Virtual Water Trade Balance and Sustainable Development using the Gravity Model An Explanation - sepideh ameri golestan; sadegh bakhtiari; Sara Ghobadi (پژوهشهای اقتصادی)
Aim and Introduction Water crisis is considered as one of the biggest challenges that most regions of the world, especially Iran, are facing. Indiscriminate surface and underground water extraction and successive droughts have limited water resources. Population growth has also led to an increase in demand and consumption in the water chain and food industry (especially agricultural products) and emphasizes the necessity of using virtual water as an efficient approach. According to the report of the International Panel on Climate Change (IPPC) in 2022, half of the world population faces severe water shortages at least for part of the year. Due to the centrality of the severe lack of water resources in the world, the first major United Nations conference on water was held in 2023, and in general, the decade from 2018 to 2028 was named as the "International Decade of Water for Sustainable Development". Although the water cycle changes are often evaluated only based on physical water flows and its reserves, this method is not effective on a larger scale and in relation to the global water cycle, and it also emphasizes the need to pay attention to "virtual water" flows which should be considered in addition to the physical flows of water. Methodology In order to design the patterns examined in this research, the gravity pattern has been used. This model is mainly used for the analysis of environmental effects in international trade, as it allows the consideration of variables with potential impact such as income, population, geographical distances and institutional factors in an economic framework. The gravity model was applied in this research in order to estimate the research patterns and since the current research has faced the problem of zero in the independent variables as well as zero imports from trading countries for some products, using the estimator method Pseudo Poisson Maximum Likelihood (PPML) was also used. It is worth mentioning here that PPML is a suitable method to solve the problems mentioned above. Findings According to the investigations, Iran's virtual water trade balance has a positive relationship with the bilateral exchange rate and a negative relationship with the distance and population ratio, and for the variable of GDP, this relationship is positive for other products except watermelon. Iran is also an exporter of watermelon and pistachio products and an importer of virtual water for two products of wheat and rice, and an exporter of virtual water for date products due to the fact that it is only for export. In general, it is considered a virtual water exporter. The existence of quantitative and qualitative problems in the country’s water resources and the location of Iran in an arid and semi-arid region and facing water shortage crises, is necessary to pay attention to the demand for water at the macro level and formulate basic plans for the sustainable use of water resources. Therefore, the use of virtual water trade approach by countries shows a favorable performance in relation to useful management measures. This research, while using the gravity model and the PPML estimator, studies the factors affecting the bilateral trade balance of virtual water in five major agricultural products of Iran (wheat, rice, dates, pistachios, and watermelon) in terms of sustainable development approach. Discussion and Conclusion In this research, bilateral virtual water trade about rice, watermelon, dates, wheat, and pistachio products between Iran and its major agricultural partners has been investigated. Examining the export and import data of agricultural products shows that these products are important and strategic products which include the largest amount of export and import of Iran's agriculture and the largest volume of virtual water trade. Therefore, the obtained results can be an example of the country's virtual water business. According to the investigations, Iran's virtual water trade balance has a positive relationship with the bilateral exchange rate and a negative relationship with the distance and population ratio, and for the variable of GDP, this relationship is positive for other products except watermelon. Also, the results indicate that virtual water import is more for wheat and rice products and virtual water export is more for pistachio and watermelon products. Regarding the date product, water extraction is relatively less than other studied products, and since the product is exported and the import level is very small, virtual water export is higher. In general, Iran can be considered as an exporter of virtual water over the period. Considering the existing conditions, Iran should act in order to achieve sustainable development by reducing virtual water exports and saving water resources. Since access to water resources and its optimal use and food production are among the benefits of human societies, sustainable development is considered an excellent approach that emphasizes the necessity of water resources management and its impact on human societies